1994
DOI: 10.1289/ehp.94102s1275
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of nickel carcinogenicity and occupational lung cancer.

Abstract: Recent progress in risk assessment of nickel carcinogenicity and its correlation with occupational lung cancer in nickelexposed workers is reviewed. Epidemiological investigations provide reliable data indicating the close relation between nickel exposure and high lung cancer risk, especially in nickel refieries. The nickel species-specific effects and the doseresponse relationship between nickel exposure and lung cancer are among the main questions that are explored extensively. It is also suggested that some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 79 publications
0
28
1
Order By: Relevance
“…In a similar lung cancer case-control study in Montreal [18,19], nickel was also found to be highly correlated with chromium, and the authors noted that the observed elevated risk for nickel (OR: 3.1, 95% CI: 1.9-5.0) may just as well be due to chromium, or both [18]. Also in cohort studies of nickel industries, the presence of other metals forms a major problem in evaluating nickelrelated risk [20]. Sorahan et al [21][22][23] carried out mortality studies in nickel-cadmium battery and nickel-chromium platers and found an association of lung cancer with cadmium and chromium exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar lung cancer case-control study in Montreal [18,19], nickel was also found to be highly correlated with chromium, and the authors noted that the observed elevated risk for nickel (OR: 3.1, 95% CI: 1.9-5.0) may just as well be due to chromium, or both [18]. Also in cohort studies of nickel industries, the presence of other metals forms a major problem in evaluating nickelrelated risk [20]. Sorahan et al [21][22][23] carried out mortality studies in nickel-cadmium battery and nickel-chromium platers and found an association of lung cancer with cadmium and chromium exposure.…”
Section: Discussionmentioning
confidence: 99%
“…A factor which is underestimated in fibre toxicity is the content of trace elements, which has been shown to be capable of inducing lung cancer (Bargagli et al, 2008;Baumgardt et al, 1986;Doll, 1958;Edel et al, 1990;Fukuda et al, 2004;Masironi, 1969;Shen and Zhang, 1994;Wei et al, 2014). As a matter of fact, there are both epidemiological and experimental indications that trace elements such as trace metals may provoke lung cancer (IARC, 1993;Nemery, 1990), and some researchers have claimed that asbestos fibres may play a passive role in producing diseases as carriers of trace elements (Dixon et al, 1970;Harington et al, 1967).…”
Section: Introductionmentioning
confidence: 99%
“…The main target areas are those in the respiratory system, depending on the size of nickel-containing dust particles. The coarsest particles are deposited in the nose, mouth, and larynx, whereas the finer grains can reach the bronchial tree (4,5).…”
mentioning
confidence: 99%